THE URGENCY OF SIYAQ (INTERPTRETATION OF THE WORD AL-INS AND BASYAR PERSPECTIVE OF AR-RAGHIB AL-ASHFAHANI) IN KITAB AL-MUFRODAT FI GHARIB AL-QUR'AN - Andri Arungga Sweta; Muhammad Hamzah Syubly bin Abd Hadi Kamil; Aman Ullah; Nematullo Mukhamedov (Universitas Muhammadiyah Surakarta, 2022)
Muhammad bin Idris as-Syafi'I said